2018
DOI: 10.1515/ijcre-2018-0106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural and Artificial Light on Fe(III) Organic Complexes Photolysis: Case of Fe (III)-Malonate and Fe(III)-Malate

Abstract: The photolysis of iron(III) organic complexes in the presence of natural and simulated light was a concern for the role it plays within the environment in terms of producing hydroxyl radicals able to degrade organic products. In the present work, the study focused on two iron(III) organic complexes. The characterization of these complexes by spectrometry allowed to show their stability in environment with a stability constant equal to Log β = 13.13 for the complex Fe(III)-malonate, and Log β = 20.85 for the Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These absorption characteristics are very consistent with previous literature reports, 21,22,61,98,99 and are similar to optical characteristics exhibited by other Fe III –carboxylate complexes. 34,100–102 Spectral characteristics of Fe II –ligand species presented here and in the later text may be attributed to the λ max at ∼256 nm. A previous study 103 reported the UV-vis spectra of Fe II –tannic acid complexes at acidic pH absorbing closer to 260 nm, while Fe II –cationic complexes in aprotic solutions exhibit a unique and narrow λ max at 262 nm.…”
Section: Resultsmentioning
confidence: 52%
“…These absorption characteristics are very consistent with previous literature reports, 21,22,61,98,99 and are similar to optical characteristics exhibited by other Fe III –carboxylate complexes. 34,100–102 Spectral characteristics of Fe II –ligand species presented here and in the later text may be attributed to the λ max at ∼256 nm. A previous study 103 reported the UV-vis spectra of Fe II –tannic acid complexes at acidic pH absorbing closer to 260 nm, while Fe II –cationic complexes in aprotic solutions exhibit a unique and narrow λ max at 262 nm.…”
Section: Resultsmentioning
confidence: 52%
“…[36] Consequently, we are expecting that Fe(III)/(3) solution had a spectral profile similar to other ferric complexes of -diketones. [37], [38], [39] In fact, at pH 4.5 Fe(III)/(3) solution showed the single symmetric peak of ligand at 263 nm and a shoulder band around 320 nm. Increasing pH, the absorbance of this lower wavelength peak increased till to pH > 8.5 when precipitation occurred.…”
Section: Uv-vis Spectroscopymentioning
confidence: 94%